PERBEDAAN SANITASI PENGELOLAAN RUMAH MAKAN DAN RESTORAN BERDASARKAN TINGKAT MUTU (GRADE A,B DAN C) DI KOTA MEDAN TAHUN 2013 - sepka syafdalni; wirsal hasan; irnawati marsaulina (Lingkungan dan Kesehatan Kerja, 2014)
Restaurant is a common business that drug a commerced activity instead for baverages and drinks. In this business, restaurant establish in a building or rent a half building and have several equipment for proceed of producting, service, salesing for baverages and drinks. The purpose of this research is to analize the restaurant differences of maintances system according to quality level (grade A, B, C and Without grade) held on 2013, in Medan 2013, which includes the principles of hygiene sanitation management of foods about food procurement, food storage, food management, the transport of food, food storage, food serving and sanitary facilities available. The type of this research is a descriptive survey to know difference of sanitary management of restaurants according to quality levels (grade A, B and C) on Medan, 2013, using survey technique interview and observation. The sample in this research was 8 restaurants. The result of this research shows that there are differences between higyene and sanitation for food maintances in these places restaurant grade A, B, C, and without grade in Medan 2013. Restaurants grade A, B and C already complete government regulation from PERMENKES No.1098/Menkes/VII/2003, however restaurants without yet complete the regulation. Based on the results of this research are recommended to the health department to always conduct outreach regarding hygienic sanitation of the restaurants. Perform periodic examinations of the worker / food consument and quality level (grade) of the restaurants. Keywords: sanitation, Restaurants, quality level, grade